Determinación de la calidad del agua del Río Pumacunchi para uso pecuario, entre el barrio Cevallos de Guaytacama y el barrio Chantilin de Saquisilí provincia de Cotopaxi periodo 2013 - Pastuña Chugchilan, Ángel Gerardo (2014)
This research was conducted by monitoring and analysis in a laboratory accredited by the OAE, . The river water samples were collected Pumacunchi on five different points with a distance of one kilometer from Cevallos of Guaytacama and Chantillin neigborhoods, Saquisilí Canton, Cotopaxi Province. It was carried out through dialogue and mutual organization among the members of the research. Also, it was necessary the technical experts’ advice in the field to take the situation with entire satisfaction. For water monitoring was necessary laboratory tools with samples in their natural state. A turbidity analysis was carried out where 11080C011597 HACH 2100Q portable model (Turbidimetro), two parameters dissolved: Oxygen and pH. A laboratory qualified such us OAE and Central Ecuador University Lab, Chemical Sciences Faculty were applied....